Observation of Schrinkage Indications in Excavator’s Bracket Casting Using Film Based Radiography - Sugiharto, Sugiharto; Ramadhany, Harun Al Rasyid (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2023)
Experimental studies have been conducted to examine the casting quality of the excavator’s bracket sample using film-based conventional radiography. Referenced standards are ASME Section V Article 2 and/or ASME E94 about radiographic examination. There are 26 areas that have been exposured for the entire surface of the bracket sample. Under viewing, area number 13 revealed the most severe defects. Therefore area number 13 is discussed in this study. Area number 13 of the bracket sample with the thickness of 16 mm was exposured using Co-60 gamma rays radiation source with activity of 80 Ci. The exposure was performed from the distance of 360 mm for 27 second. The D7 medium speed radiographic film was used to record the latent image of the exposured sample. The exposured film was then developed in chemical solutions to convert the latent image into permanent image or radiograph. The radiograph is analyzed using a light viewer to see whether there are any indications in the sample being examined. Under viewing, indications of distributed shrinkage in the casting body were apparently observed. These indications are fall into category of C4 according to the radiograph album of ASME E446 standard for steel casting with thickness up to 2 in. (50.8 mm). Defects of C4 are categorized as bad. The experiment concludes that the casting quality of the excavator’s bracket is poor and it is recommended that the bracket should be repaired and re-tested radiographically. Otherwise, the bracket sample is prohibited to use for services because of unsafe reason.